Les Relations entre la région du Tchad actuel et l'Afrique du Nord à l'époque médiévale (X/XVIè siècle) - Abakar, Abdel Hamid (Faculté des Sciences Humaines de Tunis, 1991)
Keywords: Commerce transsaharien

La politique économique des Kunta au Hoggar au XIX° siècle : la compétition avec le réseau de commerce ibadite pour le contrôle de la saline de l’Amadghor - Belhachemi, Faouzia (Identité, communauté, 1995)
Keywords: Commerce transsaharien

L’itinéraire d’une lignée issue de Sidi Muhammad al Kunti As-Saghir (XV°-XVI° siècles) depuis le Sahara occidental jusqu’au Damagaram - Belhachemi, Faouzia (Revue de Géographie Alpine, 1994)
Keywords: Commerce transsaharien

Les écrivains arabes du Moyen âge au sujet des mines de pierres précieuses et de pierres fines en territoire africain et de leur exploitation - Lewicki, Tadeusz (Africana Bulletin, 1967)
Keywords: Commerce transsaharien

Routes de commerce et échanges en Afrique occidentale en relation avec la Méditerranée: un essai sur le commerce africain médiéval du XIe au XVIe siècle - Devisse, Jean (Revue d'histoire économique et sociale, 1972)
Keywords: Commerce transsaharien

Routes de commerce et échanges en Afrique occidentale en relation avec la Méditerranée: un essai sur le commerce africain médiéval du XIe au XVIe siècle - Devisse, Jean (Revue d'histoire économique et sociale, 1972)
Keywords: Commerce transsaharien

Recueil des sources arabes concernant l'Afrique occidentale du VIIIe au XVIe siècle: Bilād al-Sūdān - Cuoq, Joseph (Sources d'histoire médiévale, 1975)
Pp. 55-56: extract from Ibn al-Saghīr: Tarīkh al-Aīmma al-Rustamiyyīn; 123-124: extract from Abū Zak. Ya1yà al-Warjlanī: K. al-Sīra wa-Akhbar al-Aīmma; 166-168: extract from Abū 'l-Rabīʿ Sul. al-Wisyanī: Siyar al- Wisyanī; 171-175: extract from Anonymous: Siyar al-Mashayikh; 194-196: extract from Darjīnī: Tabaqat al- Mashayikh.
Keywords: Commerce transsaharien

L'itinéraire d'Ibn Battuta en Afrique occidentale au XIVe siècle, les gens de l'or et leur idéologie - Rey, Pierre-Philippe (Terrains et engagements de Claude Meillassoux: hommages, 1998)
Keywords: Commerce transsaharien

La jonction entre réseau Ibadite Berbère et réseau Ibadite Dioula du commerce de l’or, de l’Aïr à Kano et Katsina, au milieu du XVe et la construction de l’empire Songhay par Sonni Ali Ber - Rey, Pierre-Philippe (Au contact Sahara-Sahel. Milieux et sociétés du Niger, 1994)
Keywords: Commerce transsaharien

Les commerçants ibāḍites nord-africains dans le Soudan au moyen âge - Lewicki, Tadeusz (Trudui dvadtzat’ pyatogo XXV Mezhdunarodnogo Kongressa Vostokovedov, Moskva 19-16 avgusta 1960, 1963)
Keywords: Commerce transsaharien

Pages d’histoire du commerce transsaharien : les commerçants et les missionnaires ibāḍites en Soudan occidental et central aux VIIIe-XIIe siècles - Lewicki, Tadeusz (Przeglad Orientalistyczny, 1961)
Keywords: Commerce transsaharien

Local Economy and Long Distance Trade in Medieval Sijilmasa - Messier, Ronald A (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 1993)
Keywords: Commerce transsaharien

Le commerce du Sahara - Fallot, Ernest (Questions diplomatiques et coloniales, 1903)
Keywords: Commerce transsaharien

Tripolitania, Cyrenaica, and Bilad as-Sudan: Trade relations during the second half of the nineteenth Century - Fituri, Ahmed Said (University of Michigan, 1982)
Keywords: Commerce transsaharien

Kanem, Bornu, and the Fazzan: Notes on the Political History of a Trade Route - Martin, Bradford G. (The Journal of African History, 1969)
Keywords: Commerce transsaharien

Processus d'islamisation et commerce transsaharien : Cas de Sijilmassa à l'époque midrarite du VIII au X siècle - Ramsi, Ahmed (Université Paris 8, 1994)
Keywords: Commerce transsaharien

al-Qasaba et d'autres villes de la route centrale du Sahara - Lange, Dierk; Berthoud, Silvio (Paideuma, 1977)
Trade of the Ibaḍīs of the Jabal Nafūsa with Kawar p. 34-36.
Keywords: Commerce transsaharien

Ancient Trade Routes from Carthage into the Sahara - Kuhn De Prorok, Byron (Geographical Review, 1925)
Keywords: Commerce transsaharien

The Myth of Trans-Saharan Trade during the Roman Era - Swanson, John T. (The International Journal of African Historical Studies, 1975)
Keywords: Commerce transsaharien

Ifriqiya as a Market for Saharan Trade from the Tenth to the Twelfth Century A.D. - Brett, Michael (The Journal of African History, 1969)
Keywords: Commerce transsaharien

Soninke-Ibāḍiyya interactions in the western Sudan c. ninth to c. eleventh century - Perinbam, B. Marie (The Maghreb Review, 1989)
This paper investigates cultural interactions between the Soninke of Ghana (or Wagadu kingdom) and the Maghribī Ibāḍiyya in the western Sudan, from about a century before, to approximately a century after the Almoravid confederation in the western Sahara. From the late 8th and early 9th centuries, the Ibāḍiyya, together with other Berberophone populations, moved south into the upper Senegal and Niger river regions, primarily engaging in commercial and missionary activities. They usually stayed in towns or Muslim quarters near urban settlements such as Tahert, Wargla, and Gao, where they came into contact with Soninke traders. The degree to which Soninke-speakers may have been influenced by the Ibāḍī religion is not clear, but available evidence suggests that some pre-Almoravid conversions occurred. However, after the 11th century, the Almoravids effectively removed most traces of the Ibāḍī doctrine (Catalogue African Studies Centre, Leiden).
Keywords: Commerce transsaharien

Were the Maghribi Ibāḍiyya contributors to West-African food production? An evaluation of the evidence - Perinbam, B. Marie (The Maghreb Review, 1987)
While acknowledging that sub-Saharan Africa was the site of early food production, this paper evaluates the evidence that the production of some North-African Mediterranean and Asian food crops was introduced into West Africa by the little known Ibāḍiyya -the oldest of all Islamic sects- from Maghribian communities, possibly between the 8th and 16th centuries. In answering the question “how” or “by what process” Maghrib foods were diffused across the Sahara, the paper argues for the existence of Ibāḍī diasporas before the 10th century when Trans-Saharan commercial networks first began to be organized, thereby fueling important changes in the desert’s political economy (Catalogue African Studies Centre, Leiden).
Keywords: Commerce transsaharien

The role of the Sahara and Saharians in relationships between North and South - Lewicki, Tadeusz (General history of Africa: Africa from the Seventh to the Eleventh century, 1988)
Keywords: Commerce transsaharien

العلاقات الأقتصادية والثقافية ببن الدولة الرستمية وبلدان جتوب الصحراء الكبرى وائرها في نشر الإسلام هناك - الحرير, ادريس صالح (مجلة البحوث التاريخية, 1983)
Keywords: Commerce transsaharien

Les origines et l’islamisation de la ville de Tādmakka d’après les sources arabes - Lewicki, Tadeusz (Revue française d'histoire d'outre-mer, 1979)
the town of Tādmakka was an important Berber market lying on the southern edge of the Sahara in the area of the Adrar of Hoghas. The vast ruins of this town called El Souq are still visible. Tādmakka maintained relations at a great distance. According to al-Bakrī (1068), the caravan routes linked it with the towns of Qayrawān and Tripoli on the one hand and with the great political and trade centres of the western Sudan, Kawkaw (Goa) and Ghāna (Kumbi Saleh), on the other. Tādmakka was already flourishing in the 9th century. It was there that was born about 884, Abū Yazīd Makhlad b. Kaydād, the famous “man with an ass”, who was the son of a Berber merchant from Bilād al-Jarīd and belonging to a branch of the Zanāta. The Ibāḍī sources note also the presence of other Berber-Ibāḍī merchants from Zanāta, sometimes very rich. According to Ibn Ḥawqal (973-975) the inhabitants of the kingdom of Tādmakka called Banū Tānmak (Tādmak) belonged to a branch of the Ṣanhāja and were of black origin crossed with whites. On the contrary, the inhabitants of the capital of the kingdom, whom Yāqūt calls Zakrām (Akrām, for Aghram: castle) were of Zanāta origin. They were mostly Ibāḍī merchants from Djerid and other Ibāḍī districts of North Africa. As for the Ṣanhājan inhabitants of the Tādmakka kingdom, they long remained pagans and only became Moslem in the year 1109-1110, after the islamization of the town of Ghāna.
Keywords: Commerce transsaharien

Les liaisons maghrébines sahariennes et soudanaises de la ville de Ouargla au Moyen Āge - Lewicki, Tadeusz (Etudes maghrébines et soudanaises, 1976)
Keywords: Commerce transsaharien

Traits d’histoire du commerce transsaharien: Marchands et missionnaires ibāḍites en Soudan occidental et central au cours des VIIIe-XIIe siècles - Lewicki, Tadeusz (Etnografia, 1964)
Keywords: Commerce transsaharien

Quelques extraits inédits relatifs aux voyages des commerçants et des missionaires ibāḍites nord-africains au pays du Soudan occidental et central au Moyen Âge - Lewicki, Tadeusz (Folia Orientalia, 1960)
Extracts with detailed annotations from: - Abū Zakariyyā’ Yaḥyà b. Abī Bakr al-Warjlānī: Kitāb al-Sīra wa-Akhbār al-A’imma (4-7); - Abū ‘l-Rabīʿ Sul. b. ʿAbd al-Sallām al-Wisyānī: Kitāb al-Siyar (10-17); - Anonymous: Siyar al-Mashāyikh (18-27). On pp. 2-4, 7-10, 17-18 detailed information on the authors and on the MSS (from the Smogorzewski collection, in 1960 in Cracow).
Keywords: Commerce transsaharien

A Trans-Saharan Caravan Route in Herodotus - Carpenter, Rhys (American Journal of Archaeology, 1956)
Keywords: Commerce transsaharien

العلاقات التجارية بين المغرب والسودان عبر الصحراء من القرن 6 الى القرن 8ه ودور تلمسان فى هذا الميدان - عطا الله, دهينة (الأصالة, 1975)
Keywords: Commerce transsaharien

La question du transsaharien après la guerre - Fallot, Ernest (Revue économique internationale, 1921)
Keywords: Commerce transsaharien

Jerba, Bou-Grara et la question du commerce transsaharien, à la fin du XIXe Siècle - ʿAnnābī, Ḥasan al- (Actes du colloque sur l’histoire de Jerba (Avril 1982), 1986)
Keywords: Commerce transsaharien

Les communications sahariennes voies d'empire - Demoulin, F. (Annales de Géographie, 1939)
Keywords: Commerce transsaharien

L'État nord-africain de Tāhert et ses relations avec le Soudan occidental à la fin du VIIIe et au IXe siècle - Lewicki, Tadeusz (Cahiers d'études africaines, 1962)
Keywords: Commerce transsaharien